A comparative study of the Schwarzschild metric tensor and the Howusu metric tensor using the radial distance parameter as a measuring index - Obaje, VIivian Onechojo (Journal of Physics: Theories and Applications, 2023)
The Einstein Curvature Tensor   using Schwarzschild Metric Tensor and the Howusu Metric Tensor were investigated. The Einstein Curvature Tensor  derived from the Howusu Metric Tensor were compared to the Einstein Curvature Tensor derived from the Schwarzschild Metric Tensor. Results of the analysis indicated that the behavior of the Howusu   were, to a large extent behaved differently from that of the Schwarzschild in the limit as the radial distance .Similar results were also obtained in the limit as .